Sustainability integration of RASE-CARD kit in determining the types of organic chemical reactions / Maira Mahmad ... [et al.] - Mahmad, Maira; Mansor, Ramanurbaya; Jye, Mark Haur; Sabarudin, Siti Adilah (2020)
RASE-CARD kit, a toolkit designated containing compilation of all RASE-CARD materials. The innovation started with the production of flash cards called a RASE-CARD, which are mnemonic to Rearrangement, Addition, Substitution and Elimination CARD. We then developed it into a digital display, known as virtual RASE-CARD kit consisting five items of RASE-CARD teaching aid, RASECARD assimilation video, RASE-CARD animated video, RASE-CARD PowerPoint notes and RASECARD online quiz. The sustainability integration of this RASE-CARD kit aims to overcome the problem of students' weakness in stating the type of organic chemical reaction correctly in the most efficient approach. A preliminary survey using pre-test on 58 students of the Two Semester System (SDS) of Negeri Sembilan Matriculation College from S2DP4, S2DP5 and S3AP2 classes found that 17 of them got grade C marks and below, which is in the percentage range between 0 to 54. All of these students were unable to identify the differences in the given chemical reaction equations and subsequently led to the failure in determining the type of organic chemical reaction. The results show that this RASE-CARD kit successfully helped the students with an increase in the mean post-test score of 9.64, in which all 17 students obtained marks at an excellent level. This RASE-CARD kit has impacted as a best teaching and facilitating approach to determine the types of organic chemical reactions with its simple, effective and user-friendly principle.